The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3922/j.psns.2014.040
|View full text |Cite
|
Sign up to set email alerts
|

Visual estimation of apertures for wheelchair locomotion in novices: Perceptual judgment and motor practice.

Abstract: The aim of the present study was to determine the effects of motor practice on visual judgments of apertures for wheelchair locomotion and the visual control of wheelchair locomotion in wheelchair users who had no prior experience. Sixteen young adults, divided into motor practice and control groups, visually judged varying apertures as passable or impassable under walking, pre-practice, and post-practice conditions. The motor practice group underwent additional motor practice in 10 blocks of five trials each,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…The results revealed that participants required a larger gap when they actually walked through the gap than when they made verbal judgments from a stationary point of observation. Significant differences between perceptual judgments and actual performance have been documented in terms of whether a stair is low enough to be stepped upon ( Warren, 1984 ), an object is close enough to be grasped (e.g., Carello et al, 1989 ; Wagman and Morgan, 2010 ), an expanse can be stepped or leaped over ( Cole et al, 2013 ; Day et al, 2015 ), the slope of a surface is small enough for it to be ascended ( Kinsella-Shaw et al, 1992 ), and wheelchair users can pass through a gap (e.g., Higuchi et al, 2004 ; Stoffregen et al, 2009a ; Rodrigues et al, 2014 ).…”
Section: Individual Factorsmentioning
confidence: 99%
“…The results revealed that participants required a larger gap when they actually walked through the gap than when they made verbal judgments from a stationary point of observation. Significant differences between perceptual judgments and actual performance have been documented in terms of whether a stair is low enough to be stepped upon ( Warren, 1984 ), an object is close enough to be grasped (e.g., Carello et al, 1989 ; Wagman and Morgan, 2010 ), an expanse can be stepped or leaped over ( Cole et al, 2013 ; Day et al, 2015 ), the slope of a surface is small enough for it to be ascended ( Kinsella-Shaw et al, 1992 ), and wheelchair users can pass through a gap (e.g., Higuchi et al, 2004 ; Stoffregen et al, 2009a ; Rodrigues et al, 2014 ).…”
Section: Individual Factorsmentioning
confidence: 99%